Epigenetics and personalized medicine: prospects and ethical issues. (July 2013) - Chadwick, Ruth; O'Connor, Alan
As scientific knowledge about gene–environment interactions and the role of epigenetic factors in gene expression grows, new possibilities for personalized medicine may be opened up. In particular, the associations that have been demonstrated between epigenetic markers and certain diseases are an exciting development for personalized medicine. These advances also create new ethical challenges, regarding causal and moral responsibility, due to unique characteristics of how epigenetic effects regulate gene expression, are established and may change over the course of a person's life. This article examines the ethical implications of integrating epigenetic knowledge into personalized medicine.